2020
DOI: 10.1039/c9ra10037g
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of glycerol monooleate with the antimicrobial peptide LL-37: a molecular dynamics study

Abstract: Molecular dynamics simulations of glycerol-monooleate (GMO)/LL-37 nanocarriers show that hydrophobic interactions among the molecules drive the formation of GMO/LL-37 micelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 87 publications
(142 reference statements)
0
3
0
Order By: Relevance
“…This result is interesting because peptides with longer hydrocarbon chains are expected to have a higher affinity for membranes via enhanced hydrophobic interactions with lipid acyl chains . A possible explanation for these differences in binding affinity is that longer side chains exhibit a larger decrease in conformational entropy caused by the transfer from the water phase to the membrane surface with restricted molecular motion, as observed in lipid–peptide, peptide–peptide, and protein–protein interactions. The decrease in the affinity of C4 and C6 peptides suggests that nonspecific binding of the peptide to the lipid membrane was suppressed in a neutral pH environment.…”
Section: Resultsmentioning
confidence: 97%
“…This result is interesting because peptides with longer hydrocarbon chains are expected to have a higher affinity for membranes via enhanced hydrophobic interactions with lipid acyl chains . A possible explanation for these differences in binding affinity is that longer side chains exhibit a larger decrease in conformational entropy caused by the transfer from the water phase to the membrane surface with restricted molecular motion, as observed in lipid–peptide, peptide–peptide, and protein–protein interactions. The decrease in the affinity of C4 and C6 peptides suggests that nonspecific binding of the peptide to the lipid membrane was suppressed in a neutral pH environment.…”
Section: Resultsmentioning
confidence: 97%
“…Further molecular dynamic simulations confirmed these experimental results, revealing that charged amine and guanidium groups from LL-37 are responsible for facilitating the interaction with the bacterial membrane. Moreover, LL-37 stabilized the cubosome through hydrophobic interactions, while polar residues remained in solution [155].…”
Section: Polymeric Nanoparticles Nanoemulsions and Micellesmentioning
confidence: 99%
“…By forming liposome-like assemblies, they form a stable structure and protect themselves against proteases, resulting in increased activity. Malini et al, demonstrated the enhanced antimicrobial activity of the self-assembled LL-37 peptide with the amphiphilic lipid glycerol monooleate [ 84 ]. The C-terminally myristoylated HD5-assembled nanobiotic displayed significantly improved broad-spectrum antibacterial activity in vitro and selective toxicity against E. coli and MRSA, with negligible hemolytic activity and low toxicity [ 85 ].…”
Section: Nanodelivery Systemmentioning
confidence: 99%